Smartphone electrocardiogram for detecting atrial fibrillation after a cerebral ischaemic event: a multicentre randomized controlled trial - KENG TAT, KOH; WAN CHUNG, LAW; WIN MOE, ZAW; PING FOO, HUI; CHEN TING, TAN; STEVEN, ANDERSON; DESMOND, SAMUEL; TEH LOM, FAM; CHING HUA, TAN; ZHAI SING, WONG; XAVIAR, SIVARAJ; CHANDAN DEEPAK, BHAVNANI; et al. (Oxford Academic, 2021)
Aims: Atrial fibrillation (AF) is a preventable cause of ischaemic stroke but it is often undiagnosed and undertreated. The utility of smartphone electrocardiogram (ECG) for the detection of AF after ischaemic stroke is unknown. The aim of this study is to determine the diagnostic yield of 30-day smartphone ECG recording compared with 24-h Holter monitoring for detecting AF ≥30 s.